p53 Promotes Cancer Cell Adaptation to Glutamine Deprivation by Upregulating Slc7a3 to Increase Arginine Uptake - Xazmin H. Lowman; Eric A. Hanse; Ying Yang; Mari B. Ishak Gabra; Thai Q. Tran; Haiqing Li; Mei Kong (Cell Reports, 2019)
Summary: Cancer cells heavily depend on the amino acid glutamine to meet the demands associated with growth and proliferation. Due to the rapid consumption of glutamine, cancer cells frequently undergo glutamine starvation in vivo. We and others have shown that p53 is a critical regulator in metabolic stress resistance. To better understand the molecular mechanisms by which p53 activation promotes cancer cell adaptation to glutamine deprivation, we identified p53-dependent genes that are induced upon glutamine deprivation by using RNA-seq analysis. We show that Slc7a3, an arginine transporter, is significantly induced by p53. We also show that increased intracellular arginine levels following glutamine deprivation are dependent on p53. The influx of arginine has minimal effects on known metabolic pathways upon glutamine deprivation. Instead, we found arginine serves as an effector for mTORC1 activation to promote cell growth in response to glutamine starvation. Therefore, we identify a p53-inducible gene that contributes to the metabolic stress response. : Lowman et al. show that glutamine deprivation induces Slc7a3 to increase intracellular arginine levels in a p53-dependent manner. This induction transiently sustains mTORC1 activity and contributes to cellular adaptation to low glutamine conditions. Keywords: p53 activation, Slc7a3, glutamine deprivation, arginine